Implementation and clinical effectiveness of a community-based non-communicable disease treatment programme in rural Mexico: a difference-in-differences analysis. Issue 6 (25th April 2018) - Duan, Kevin; McBain, Ryan; Flores, Hugo; Rodriguez Garza, Francisco; Nigenda, Gustavo; Palazuelos, Lindsay; Palazuelos, Daniel; Moreno Lázaro, Elena; Enríquez Ríos, Natán; Elliott, Patrick F
Abstract: Non-communicable diseases (NCDs) account for the five largest contributors to burden of disease in Mexico, with diabetes representing the greatest contributor. However, evidence supporting chronic disease programmes in Mexico is limited, especially in rural communities. Compañeros En Salud (CES) partnered with the Secretariat of Health of Chiapas, Mexico to implement a novel community-based NCD treatment programme. We describe the implementation of this programme and conducted a population-based, retrospective analysis, using a difference-in-differences regression approach to estimate the impact of the programme. Specifically, we examined changes in diabetes and hypertension control rates between 2014 and 2016, comparing CES intervention clinics ( n = 9) to care-as-usual at non-CES clinics ( n = 806), adjusting for differences in facility-level characteristics. In 2014, the percent of diabetes patients with this condition under control was 36.9% at non-CES facilities, compared with 41.3% at CES facilities ( P > 0.05). For hypertension patients, these figures were 45.2% at non-CES facilities compared with 56.2% at CES facilities ( P = 0.02). From 2014 to 2016, the percent of patients with diabetes under control declined by 9.2% at non-CES facilities, while improving by 11.3% at non-CES facilities where the Compañeros En Salud Programa de Enfermedades Crónicas intervention was implemented ( P < 0.001). Among hypertension patients, those with the condition under control increased by 21.5% at non-CES facilities between 2014 and 2016, compared with 16.2% at CES facilities ( P > 0.05). Introduction of the CES model of NCD care was associated with significantly greater improvements in diabetes management between 2014 and 2016, compared with care-as-usual. Hypertension control measures were already greater at CES facilities in 2014, a difference that was maintained through 2016. These findings highlight the successful implementation of a framework for providing NCD care in rural Mexico, where a rapidly increasing NCD disease burden exists.